Co-design for social innovation and organisational change : Developing horizontal relationships in a social enterprise through walking - Calvo, Mirian; Sclater, Madeleine (My University, 2020)
Although an emerging body of literature identifies co-design as a promising approach to addressing the most urgent social challenges, little research has been undertaken about how co-design can support social change within the communities and organisations with which they collaborate. This is important because behavioural and organisational change is usually associated with the emergence of social innovations. These pressing socio-cultural challenges require interdisciplinary expertise, and we argue that the practice of co-design is an approach that provides such expertise. Co-design by its nature is collaborative and can respond to the cultural demands of a society eager to participate. These demands require significant research to better understand how the practice of co-design can be a catalyst for social change and social innovation. In this paper, we explore what is meant by co-creation, social design, and co-design within the theoretical context of this study. We present a case study that focuses on a social enterprise committed to sustainability operating within the Highlands and Islands of Scotland. Here we examine the transformative process - associated with co-design - that the social enterprise and its members encountered. Participatory Action Research (PAR) was implemented as the research approach to this study informed by ethnographic and co-design methods. The analysis suggests that the co-design process empowered the social enterprise and its members, enabling them to co-develop responsive and empathetic attitudes among themselves. Co-design supported organisational changes by nurturing collaborative attitudes, expanding perspectives about social issues and releasing latent human abilities and assets.
Keywords: Participatory design; Co-creation; Social design; Design for social change; Co-design; Mutual learning; Social innovation